2019
DOI: 10.3892/etm.2019.8134
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2.5 insufficiency leads to atrial electrical remodeling through Wnt signaling in HL‑1 cells

Abstract: Homeobox protein Nxk-2.5 (Nkx2.5) is a homeobox transcription factor that promotes chamber-like myocardial gene expression. Data from a previous genome-wide association study suggested that Nkx2.5 may be associated with the genetic variation that underlies atrial fibrillation (AF). Nkx2.5 loss of function has been demonstrated to be associated with an increasing susceptibility of familial AF. Therefore, the aim of the present study was to investigate the effect of Nkx2.5 loss of function on electrophysiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The homeobox transcription factor Nkx2.5 is implicated in heart development and growth and was shown to be associated with a genetic variation that underlies AF. 48 In HL-1 cardiomyocytes, silencing of Nkx2.5 resulted in decreased expression of Wnt11 49 which is in line with the crucial function of Wnt signaling in development.…”
Section: Genetic Factorsmentioning
confidence: 58%
“…The homeobox transcription factor Nkx2.5 is implicated in heart development and growth and was shown to be associated with a genetic variation that underlies AF. 48 In HL-1 cardiomyocytes, silencing of Nkx2.5 resulted in decreased expression of Wnt11 49 which is in line with the crucial function of Wnt signaling in development.…”
Section: Genetic Factorsmentioning
confidence: 58%
“…Studies have shown that Shox2-knockout mice died during pregnancy due to cardiac conduction system defects, including SAN and valve sinus hypoplasia accompanied the loss of T-box transcription factor 3 and HCN4 expression and ectopic natriuretic peptide A, connexin 40, and NKX2-5 expression in the SAN, which suggested that the differentiation of SAN failed in Shox2-knockout mice, and the cells in SAN area differentiated into working cardiomyocytes instead of P cells [29]. The regulation of SHOX2 on downstream BMP4, GATA4 and NKX2-5 is helpful to promote the expression of HCN4 and CAV3.1, which is of great significance for maintaining the pacing function of SAN and inhibiting the transformation of P cells into working cardiomyocytes [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Rats displayed a reduced level of Nkx2.5, particularly in the left atrium, after coronary artery ligation. Moreover, the RNA interference strategy was successful in decreasing NKX2.5 mRNA transcript and protein, enhancing the expression of HCN4 and almost silencing Cx40, SERCA, phospholamban, and Cav1.2, all proteins fundamental in Ca 2+ handling [278].…”
Section: Modeling Of Af-related Nppa Mutationsmentioning
confidence: 99%